The Role of c-ERBB2(Her-2) and P53 in Differentiating Low Grade from High Grade Urothelial Carcinoma of Urinary Bladder - Roaa Salih Mahdi (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Urothelial carcinoma of the urinary bladder, represents 90% of all primary tumors of this organ, and one of the most common ten malignancy in Iraq and world wide. These tumors can range from low grade papillary neoplasms to less frequent more aggressive and invasive solid tumors. More than 70% of superficial tumors recur, and about one-third of the patients have tumor progression, which can affect the quality of their life HER-2\neu receptor as an important growth factor . This receptor possesses intrinsic tyrosine kinase activity and all members of this family are frequently overexpressed and \or their respective genes are amplified in human neoplastic tissue . Its overexpression has been associated with high grade and advanced stage of bladder carcinoma specially TCC. Altered expression of the p53 gene has also been associated with transitional cell carcinoma. Materials and Methods: 62 patients with TCC were included in this study and conducted in the Department of Pathology, Faculty of Medicine, Kufa University during the period from January 2012 through April 2013. EnVision method (polymer based immunohistochemistry) was used for the immunohistochemical detection of p53 and Her_2/neu. Results: HER-2\neu overexpression was found in 62.9% of bladder carcinoma , and no expression in benign bladder lesions (cystitis) was detected , (P value < 0.05) . HER-2\neu overexpression and its intensity were well correlated to grade of tumor indicating that HER-2\neu positive bladder carcinoma are biologically aggressive and detected more frequent in grade III than grade I or grade II (P value < 0.05, R = 0.0181).P53 was expressed in (66.12%) of bladder carcinoma , and no expression in benign bladder lesions (cystitis) was detected , (P value < 0.05) . P53 overexpression and its intensity were well correlated to grade of tumor indicating that P53 positive bladder carcinoma are biologically aggressive and detected more frequent in grade III than grade I or grade II (P value < 0.05, R = 0.0821). Conclusions: From the above results we concluded that p53 and Her_2/neu over-expression play an important role in pathogenesis of urothelial carcinoma evolution, as their positivity associated with higher tumor grade.